Experiential theatres : praxis-based approaches to training 21st century theatre artists - Lewis, William W.; Bartley, Sean (New York, NY : Routledge, 2023)
"Experiential Theatres is a collaboratively edited and curated collection that delivers key insights into the processes of developing experiential performance projects and the pedagogies behind training theatre artists of the twenty-first century. Experiential refers to practices where the audience member becomes a crucial member of the performance world through the inclusion of immersion, participation, and play. As technologies of communication and interactivity have evolved in the postdigital era, so have modes of spectatorship and performance frameworks. This book provides readers with pedagogical tools for experiential theatre making that address these shifts in contemporary performance and audience expectations. Through case studies, interviews, and classroom applications the book offers a synthesis of theory, practical application, pedagogical tools, and practitioner guidance to develop a praxis-based model for university theatre educators training today's theatre students. Experiential Theatres presents a holistic approach for educators and students in areas of performance, design, technology, dramaturgy, and theory to help guide them through the processes of making experiential performance"--
Keywords: Theater -- Study and teaching (Higher); Experimental theater; Participatory theater; PERFORMING ARTS / Theater / Direction & Production; GAMES / Video & Electronic